(untitled) (Medico Legal Update, 2021)
Foster Family Toddlers (FFT) as an effort program to improve the knowledge and skills of parents fostering the development of children in a whole and optimal way. The result of 2018 Basic Health Research, East Java Province shows the percentage low birth weight is 6.5%, underweight of toddler is 15%, wasting of toddler is 8% and the coverage of exclusive breast milk is 40%. East Java Health Profile 2018 showed of low birth weight is 3,7% and the coverage of exclusive breast is 76.83%, underweight and wasting in toddler is not found numbers, but there is the weight of toddler in under red line is 0.77%. Therefore, needs to know trend of the implementation of FFT in East Java. This study was quantitative descriptive research design with secondary data. The result showed the reporting of FFT group from 2015-2017 increased by 4.52% and decreased in 2017-2019 by 4.52% and has not reached the target of KKP 80%. FFT member participation in 2015-2017 increased by 3.78% and decreased in 2017-2019 by 12.55%. FFT family attendance at the 2015-2016 Meeting increased by 1.38% and decreased in 2016-2019 by 1.24%, and the family of members of FFT Child Card Users in 2015-2019 saw a continuous increase of 9.52%. So the result of the trend of the implementation of activities is less maximal because there are still some obstacles to be considered.